Associations between body composition and fundamental motor skill competency in children - E. Kipling Webster; Indica Sur; Alicia Stevens; Leah E. Robinson (BMC, 2021)
Abstract Background Evidence supports an inverse relationship between weight status and motor competence, but most work utilizes body mass index as the proxy for weight status. Body mass index fails to account for essential components of body composition, which may be critical for motor performance. The purpose of this investigation was to examine the relationship between fundamental motor skills competency and body composition (i.e., fat mass, fat percentage, and fatfree mass) as measured by bio-electrical impedance analysis and body mass index in children. Methods Two hundred forty-four children from the Southeastern portion of the United States participated in this project (6.05 ± 2.01 years, 53.3% male). Fundamental motor skills were measured using the Test of Gross Motor Development - 2nd edition and body composition was assessed with the Tanita SC-331S Body Composition Analyzer (bio-electrical impedance analysis). Body mass index was calculated using CDC normative growth charts. Results Bio-electrical impedance analysis measures accounted for 23.1%, F(3, 241) = 24.10, p < .001 and 2.7%, F(3, 241) = 2.22, p = .086 variance in locomotor and object control subscales, respectively; body mass index accounted for 8.4% (locomotor) and 0.1% (object control) variance. For the Test of Gross Motor Development -2nd edition total score, bio-electrical impedance analysis measures accounted for 24.4% F(3, 241) = 25.90, p < .001 compared to body mass index which accounted for 7.9% F(1, 244) = 20.86, p < .001 of the variance. Only fat free mass (p < .001) was a significant predictor for locomotor skills and total models for the Test of Gross Motor Development - 2nd edition; BMI was also a significant predictor (p < .001) in both the locomotor and total models. Conclusions Different components of body composition (i.e., fat free mass) were associated with different aspects of fundamental motor skills competency. Excess body fat may be a morphological constraint to proficient locomotor performance when transporting the body through space. In contrast, body composition did not significantly predict object manipulation performance. More work is needed to understand the causality and directionality of this relationship; however, bio-electrical impedance analysis accounts for more variance in fundamental motor skills performance than body mass index in a field-based setting.